O życiu rodzinnym i edukacji córek księcia Franciszka Ksawerego de Saxe w świetle dokumentów Archives départemantales de l’Aube - Jakuboszczak, Agnieszka (Biuletyn Historii Wychowania, 2012)
Francis Xavier of Saxony, the son of Augustus III, Elector of Saxony and King of Poland, left a very extensive correspondence, which has been preserved until our times in the Departmental Archives in Troyes. The collection constitutes a very important source for the history of everyday life and the history of education of aristocracy in the 18th century. A part of the collection is available in the electronic version on the website of the Archives. Numerous children of the Prince, the sons, as well as daughters, obtained the education suitable for the royal family – comprehensive, competent, pursuing the spirit of the Enlightenment. The period of pursuing knowledge by the children of Francis Xavier was not the time of severing the ties with the parents. The relationships between the father and his sons and daughters were lasting and became more intense in the course of time. Carefully selected tutors and governesses were a very important link between the Prince and his wife and the children. Preceptors not only controlled the educational progress, but also every aspect of daily life, especially of the girls. The Prince expected detailed reports which facilitated control over the adolescent boys and girls, for whom best matches for marriage were being arranged. A complex world of relationships of Francis Xavier’s family completes for us the picture of everyday life of the ruling families, so often confined by the tight restraints of the ceremonial.